Urban workers’ experiences in consuming C-Drama: An interpretative phenomenological analysis approach - Muhammad Rizky; Edoardo Irfan (Priviet Social Sciences Journal, 2026)
The rise of Chinese micro-dramas on digital streaming platforms has created a genuinely new mode of urban media consumption—one that has barely been studied. This paper examines how office workers in Greater Jakarta (Jabodetabek) experience consuming Chinese micro-dramas, paying particular attention to how this format functions as a tool for escapism, emotional regulation, and identity negotiation within demanding professional routines. Using an Interpretative Phenomenological Analysis (IPA) design, data were gathered through in-depth semi-structured interviews with two purposively selected participants: an HR Generalist and an Accounting Assistant Manager, both active consumers of micro-drama content on platforms including TikTok, WeTV, and YouTube Shorts. Analysis produced four superordinate themes: (1) Motivational Escapism and Emotional Regulation, in which micro-dramas operate as psychological safe spaces through predictable, wish-fulfilling narratives; (2) Interstitial Consumption Patterns, reflecting a multi-platform viewing practice that slots viewing into the fragmented gaps of urban professional schedules; (3) Resonance of Materialism and Career Themes, in which the dominant visual economy of wealth and instant social mobility functions as aspirational compensation for rigid corporate realities; and (4) Identity Tensions and Critical Reflection, revealing productive tensions between entertainment satisfaction, productivity guilt, and gender-based social barriers to disclosure. The findings extend the growing literature on transnational media reception in Southeast Asia and carry practical implications for digital media industry localization strategies.